VD_FINDINFO AP / 2011 / 130 vom 11. Mai 2009 - VD Tribunal cantonal (2009)
BAIL À LOYER, DÉFAUT DE LA CHOSE, TRAVAUX DE CONSTRUCTION, ACTION EN RÉDUCTION | 256 al. 1 CO, 259a CO, 259d CO, 451 ch. 2 CPC, 452 al. 2 CPC, 13 LTB